1993
DOI: 10.1007/bf01309536
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylation of Semliki Forest virus glycoproteins in insect cells (C 6/36) occurs in an early compartment and is coupled to the cleavage of the precursor p 62

Abstract: The acylation of the envelope proteins of Semliki Forest virus by palmitic acid in infected mosquito (C6/36) cells was investigated. It is shown that in these cells palmitic acid was incorporated post-translationally via hydroxylamine-labile linkages onto cysteines in the inner domains of the viral envelope proteins. The kinetics of incorporation, however, differed considerably as compared to higher eukaryotic cells. (i) The precursor of the envelope proteins E2 and E3, p62, was weakly and incompletely palmito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Acylation of E1 and E2 is also involved in alphavirus budding [46], [47], but was not investigated in this work due to the documented ability of insect cells to palmitoylate the glycoproteins of AcMNPV, Marburg virus, and SFV [48],[49], [50]. Taken together, these observations suggested that Sf 21 cellular or culture conditions were influencing the conformation and stability of the E1/E2 complex thought to be involved in budding [21].…”
Section: Resultsmentioning
confidence: 99%
“…Acylation of E1 and E2 is also involved in alphavirus budding [46], [47], but was not investigated in this work due to the documented ability of insect cells to palmitoylate the glycoproteins of AcMNPV, Marburg virus, and SFV [48],[49], [50]. Taken together, these observations suggested that Sf 21 cellular or culture conditions were influencing the conformation and stability of the E1/E2 complex thought to be involved in budding [21].…”
Section: Resultsmentioning
confidence: 99%
“…For example, the SFV glycoprotein E2 is palmitoylated close to its transmembrane domain (Scharer et al, 1993) but is not transported to MLMs. Palmitoylation might therefore be overruled by additional sorting signals in proteins that are not destined for myelin.…”
Section: Discussionmentioning
confidence: 99%
“…7). As acylation of E~ takes place in the ER of C6/36 cells even at 8 °C [38] the two bands of E1 were tentatively identified as follows: Lower band: newly synthesized Ea containing a high mannose type glycan; upper band: acylated E1 with a high mannose type glycan. At higher temperatures, additional bands appear corresponding to the glycosylated and trimmed virion forms [29].…”
Section: Discussionmentioning
confidence: 98%
“…For the analysis of intracellular protein complex formation the viral protein complexes were isolated by sucrose density gradient centrifugation as described recently [38]. Gradient fractions were then analysed by SDS-PAGE and evaluated by densitometric scanning.…”
Section: Isolation Of Protein Complexesmentioning
confidence: 99%